2018
DOI: 10.3390/mi9090473
|View full text |Cite
|
Sign up to set email alerts
|

LED Optrode with Integrated Temperature Sensing for Optogenetics

Abstract: In optogenetic studies, the brain is exposed to high-power light sources and inadequate power density or exposure time can cause cell damage from overheating (typically temperature increasing of 2 ∘C). In order to overcome overheating issues in optogenetics, this paper presents a neural tool capable of assessing tissue temperature over time, combined with the capability of electrical recording and optical stimulation. A silicon-based 8 mm long probe was manufactured to reach deep neural structures. The final p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Prior to this work, some resistor and RTD-based temperature sensors are reported to monitor the temperature in brain, retina and myocardium [1114]. Goncalves et al reported an optrode with an integrated temperature sensor based on RTD [14]. The implemented 3D probe has positioned RTD on the opposite side of the LED to reduce the distance between the heating source (LED) and the thermal sensor (RTD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to this work, some resistor and RTD-based temperature sensors are reported to monitor the temperature in brain, retina and myocardium [1114]. Goncalves et al reported an optrode with an integrated temperature sensor based on RTD [14]. The implemented 3D probe has positioned RTD on the opposite side of the LED to reduce the distance between the heating source (LED) and the thermal sensor (RTD).…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 compares the designed temperature sensors with resistor-based temperature sensors for in vivo application, whereas only one is integrated within the optrode with LEDs for optogenetics application [14]. Our achieved temperature range is based on the measured reverse current change versus temperature variation, which is dependent on the applied bias and mainly the LED type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…202 ) and ReaCHR 203 , and halorhodopsin 204 ). In pulsed-mode operation, the maximum steady-state temperatures at the interface with the tissue are less than a few tenths of a degree Celsius 102 , which is well below the safety thresholds (2-5 °C) for irreversible tissue damage 205,206 , the 2 °C limit for neurostimulators 207 and the approximate 1 °C limit for thermal neuromodulation 208 . Such µ-ILEDs have electrical operating requirements that can be satisfied by a range of wireless power sources.…”
Section: Optogenetic Stimulationmentioning
confidence: 94%
“…To provide enhanced control during optogenetic studies, Goncalves et al [16] describe a hybrid device combining optical stimulation and neural recording, which is capable of monitoring the heat generated during light exposure. A proof-of-concept device, with double-sided function: on one side, an optrode with LED-based stimulation and Pt recording sites on one side of the probe and with a Pt-based thin-film thermoresister for temperature measurement on the opposite side, was fabricated and characterized.…”
mentioning
confidence: 99%